THE DILEMMA OF INTEREST RATE REDUCTION BY BANK INDONESIA: A LITERATURE REVIEW ON THE IMPACT ON ECONOMIC GROWTH AND RUPIAH EXCHANGE RATE STABILITY - Syahidin Syahidin; Rahma Helal Al_ Jbour; Iyad Abdallah Al-Shreifeen (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to examine the dilemma of lowering interest rates by Bank Indonesia (BI) through a literature review of its impact on economic growth and rupiah exchange rate stability. The reduction in the BI benchmark interest rate is one of the main instruments of monetary policy that is expected to encourage consumption, investment, and lending, thereby accelerating national economic growth. However, this policy also brings risks to rupiah exchange rate stability, especially due to potential capital outflows and weakening the attractiveness of rupiah-denominated assets in the eyes of foreign investors. This study uses a qualitative method with a literature review approach, analysing findings from various scientific journals, Bank Indonesia reports, and related economic publications. The results show that interest rate cuts are effective in promoting economic growth, but have the potential to increase exchange rate volatility if not balanced with adequate intervention and external risk management. Therefore, Bank Indonesia is faced with a trade-off between stimulating economic growth and protecting external macroeconomic stability, which requires prudent, measured, and coordinated policies with fiscal and macroprudential policies.